Post-Keynesian and Kaleckian thoughts on ecological macroeconomics - Giuseppe Fontana; Malcolm Sawyer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This paper outlines an approach to ecological macroeconomics based on post-Keynesian and Kaleckian ideas. It views growth as demand-driven through investment, and focuses on the conflicts between that demand-driven growth rate, the growth of the effective labour force and the 'nature constrained' rate of growth. The paper argues that there will not be 'market forces' which will address those conflicts, and specifically to bring growth to an environmentally sustainable growth rate. The policy agenda which is suggested is wide ranging and it calls for appropriate fiscal policy and budget deficits.
Keywords: Q57; E12; E51; 330; ecological economics; sustainability; post-Keynesian; Kaleckian; demand-led growth